Contemporary challenges to human rights law - Smyth, Claire-Michelle; Lang, Richard; Thompson, Jack Clayton (Cambridge Scholars Publisher, 2020)
This collection of essays highlights the many problems and challenges facing human rights law today. Bringing together academics, practitioners and NGOs, it examines some of the contemporary challenges facing human rights law and practice in England, Northern Ireland, the Republic of Ireland, France and America. It is clear that we live in a time where human rights are in crisis. A decade of austerity measures at the domestic, regional and international levels evidently has had a detrimental effect on the protection of human rights. Cuts to social spending have resulted a failing social welfar
Keywords: Human rights; Aufsatzsammlung